AN ANALYSIS ON SANJHI ART: AN EPITOME OF INDIAN FOLK ART IN MATHURA - Pooja Modanwal; Kiran Singh (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Sanjhi Art- is the popular and historical art of stencilling by way of paper cutting. It relates to the Braj Area which is situated nearby areas of Mathura. The said paper art (stencils) was and are still being utilized for creating coloured powder art which is known as “sanjhi”. The Art Form is made in the Braj temples in accordance with the rituals of the People in Mathura. It is inspired from great epics of Hindu deity i.e., Radha Krishna. In the present research paper, the author will elaborate on the historical background of the Sanjhi Art. It will further discuss the ritualistic and mythological Importance of this Art. The researcher will analyse the Sanjhi Art in a manner which has made the India, a heaven for folk art across the globe. In this paper, the researcher will further examine the shift of traditional Sanjhi to modern Snajhi which are being used for commercial purpose. The author will analyse the distinctive feature of the Sanjhi Art and efforts taken for preserving this Art in Indian Context.